2023
DOI: 10.1177/02698811231173588
|View full text |Cite
|
Sign up to set email alerts
|

The interaction between kynurenine pathway, suicidal ideation and augmentation therapy with minocycline in patients with treatment-resistant depression

Abstract: Background and aims: We investigated kynurenine pathway (KP) metabolites levels and their association with suicidal ideation in patients with treatment-resistant depression (TRD) and elevated peripheral inflammation. The effect of antidepressant augmentation with minocycline on KP metabolites was tested. Methods: We analysed data from MINocycline in DEPression, a 4-week, randomized, placebo controlled (1:1) trial of minocycline added to antidepressant treatment in 39 TRD patients ( n = 18 minocycline; n = 21 p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

3
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(10 citation statements)
references
References 49 publications
3
7
0
Order By: Relevance
“…In the unlikely event that [Trp] was not decreased in the study patients, other explanations should be sought, for example, whether KAT or kynureninase was inhibited to elevate Kyn levels. The finding by Nettis et al (2023) that QA levels are increased strongly suggests that a raised [Kyn] coupled with activation of KMO and subsequently of kynureninase occur in suicidal ideation patients. The authors found that kynurenic acid (KA) was below the limit of detection.…”
mentioning
confidence: 99%
See 4 more Smart Citations
“…In the unlikely event that [Trp] was not decreased in the study patients, other explanations should be sought, for example, whether KAT or kynureninase was inhibited to elevate Kyn levels. The finding by Nettis et al (2023) that QA levels are increased strongly suggests that a raised [Kyn] coupled with activation of KMO and subsequently of kynureninase occur in suicidal ideation patients. The authors found that kynurenic acid (KA) was below the limit of detection.…”
mentioning
confidence: 99%
“…Nettis et al (2023) reported that patients with treatment-resistant depression who exhibit suicidal ideation show a higher plasma ratio of kynurenine (Kyn) to tryptophan (Trp), which correlates with immune activation parameters. The study is clearly of interest and the authors should be commended for having measured a range of Kyn metabolites, but they have not taken advantage of the available information that could have enhanced interpretation of their findings and provided important conclusions regarding Kyn pathway (KP) dysfunction in this particular group of patients.…”
mentioning
confidence: 99%
See 3 more Smart Citations